Advances in 3D textiles - Chen, Xiaogang (Woodhead Publishing Limited, in association with The Textile Institute, 2015)
Advances in 3D Textiles presents the most recent advances in the production of three-dimensional fibrous structures and how their use has resulted in the creation of novel fabrics and applications. The text covers a wide range of fabric types, including their structures, properties, and uses in the textiles industry. Beginning with the various types of woven three-dimensional fabrics, the text then examines 3-D knitted, braided, and non-woven textiles, and the main applications and uses of three-dimensional textiles. Presents the most recent advances in the production of three-dimensional.
Keywords: Textile fabrics.; Textile design.; Composite materials.; Coated fabrics.; Air-supported structures.; elektronické knihy; electronic books